Influence of heat radiation of high intensity on thetemperature of thermally thin body; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Baktybaeva D. Dana (2015, 2015)
Title screen